Toward A Comprehensive Understanding: The Deductive Method Of Madzhab Ushul Fiqh Mutakallimin And Its Transformative Impact On Moderate Fiqh Discourse - Ahmad Munir Hamid (Universitas Islam Darul 'ulum Lamongan, 2026)
This paper examines the deductive method used by the Ushul Fiqh Mutakallimin madhhab and its implications for moderate fiqh thought. Madzhab Ushul Fiqh Mutakallimin is one of the schools of thought in the science of Ushul Fiqh which has a strong deductive approach in understanding sharia laws. This paper involves an in-depth analysis of the basic principles of the deductive method used by the Ushul Fiqh Mutakallimin madhhab, including the use of textual postulates and qiyas (analogies) in determining the laws of fiqh. In the contemporary context, moderate fiqh thought is particularly relevant in the face of the complex challenges faced by Muslims. A more flexible understanding of sharia laws can help in addressing various social and moral problems that arise in modern society. Therefore, an understanding of the deductive method of the Ushul Fiqh Mutakallimin madhhab and its implications for moderate fiqh thought has important relevance in developing fiqh insights that are in accordance with the demands of the times.